Erratum to: The influence of travel time on emergency obstetric care seeking behavior in the urban poor of Bangladesh: A GIS study [BMC Pregnancy Childbirth, 16, (2016) (240)] - Panciera, Rocco; Khan, Akib; Rizvi, Syed Jafar Raza; Ahmed, Tanvir; Islam, Rubana; Adams, Alayne M. (© 2016 BioMed Central Ltd., 2018)
This erratum was published in the BMC Pregnancy and Childbirth [© 2016 The Author(s).] and the definitive version is available at: https://doi.org/10.1186/s12884-016-1082-x The Journal's website is at: https://bmcpregnancychildbirth.biomedcentral.com/articles/10.1186/s12884-016-1082-x